Model Pembelajaran Make A Match Meningkatkan Perkembangan Kognitif dalam Mengenal Lambang Bilangan - Ni Made Desy Pratiwi Handaryani; I Ketut Pudjawan (Universitas Pendidikan Ganesha, 2021)
There are still many young children whose ability to recognize number symbols has not developed optimally. This study aims to analyze the make a match learning model on cognitive development in recognizing number symbols in group A Kindergarten child. This research was classroom action research (CAR) which was carried out in two cycles of action. The subjects of this study were group A1 kindergarten students, totaling 18 students, consisting of 8 girls and 10 boys. The observation method was used to collect data on cognitive development in recognizing number symbols. The instrument used in this study was an observation sheet. The data analysis method used is descriptive statistical analysis method and quantitative descriptive analysis method. The results of data analysis in this study showed that there was an increase in the average percentage of cognitive development in recognizing number symbols in group A1 children of 15.25%. This can be seen from the increase in the average percentage of cognitive development in recognizing children's number symbols in the first cycle of 65.25% with moderate criteria to 80.50% in the second cycle with high criteria. Based on the results of the study, it can be concluded that the application of the make a match learning model can improve cognitive development in recognizing the number symbols of children in group A.